Integration of Biofloc Cultivation and Waste Banks as a CSR Model for Inclusive Food Security in Urban Areas - Yuliendri, Mohammad; Kristiyant, Nadya Putri; Septiani, Kintan Ayu; Mulyawan, Reyhan Januar (International Journal of Social Science and Community Service, 2025)
The gap between demand and supply of local food in urban areas like Batam City triggers vulnerability to nutritional access, especially for lower-middle-income communities. In response to this challenge, PT PLN Batam - PLTGU Tanjung Uncang Unit initiated the SEHATI TABUROSI program (Environmental Synergy and Inclusive Food Security) as a Corporate Social Responsibility (CSR) model based on community empowerment. This study aims to explore the implementation and impact of the SEHATI TABUROSI program, which integrates biofloc fish farming technology, waste bank management, and strengthening women's roles in local food security. Using a qualitative case study approach, data was collected through interviews, observations, and documentation in Tanjung Uncang Village, Batam. Results show that the program successfully increased tilapia production up to 210 kg per cycle, strengthened women's economic capacity, and supported supplementary feeding programs (PMT) for vulnerable children. Organic and inorganic waste was processed into feed, fertilizer, and pond construction materials, reflecting circular economy practices. In addition to resource efficiency, direct participation of PLN Batam - PLTGU Tanjung Uncang Unit employees in technical competency transfer also strengthened program sustainability. This holistic intervention model proved effective in combining economic, social, and environmental aspects, and has the potential to be replicated in other urban areas with similar challenges.